การศึกษาผลสัมฤทธิ์ทางการเรียนรวมวงแจ๊สและความพึงพอใจที่มีต่อการจัดการเรียนการสอน ด้วยชุดการสอนการรวมวงแจ๊ส ของนักเรียนดนตรีในระดับมัธยมศึกษาตอนปลาย โรงเรียนสารสาสน์เอกตรา - สุทธิเกษม, ณัฐพล; หวังพานิช, ฌานิก (Fine Arts Journal: Srinakharinwirot University, 2019)
This research is quasi-experimental research using one-group pretest-posttest design aimed to 1) examine the learning achievement in jazz ensemble through the instructional package on jazz ensemble; and 2) study the satisfaction toward the teaching and learning through the instructional package on jazz ensemble. The sample was 20 senior high school students, Sarasas Ektra High School who enrolled in jazz ensemble class. The research tools comprised the experimental tool including the instructional package on jazz ensemble; and the data-collecting tool including the learning achievement in jazz ensemble test and the satisfaction toward the teaching and learning through the instructional package on jazz ensemble test. The results derived by comparing learning achievement in jazz ensemble through the instructional package on jazz ensemble using a statistical analysis of the t-test for dependent sample; and analysing the satisfaction toward the teaching and learning through the instructional package on jazz ensemble using a simple descriptive statistcal analysis. The results were 1) the learning achievement in jazz ensemble of the music students were significant higher than before using instructional package on jazz ensemble at the .05 level; and 2) the satisfaction of students toward the teaching and learning through the instructional package on jazz ensemble was in the high level (X= 4.36, S.D. = 0.71)